MODEL MANAJEMEN MADRASAH ALIYAH EFEKTIF (Studi pada Tiga Madrasah Aliyah di Kudus) - Fatah Syukur (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study aimed to find an effective management model madrasah, with essential elements of program planning, program implementation plans, monitoring and effective evaluation program for madrasah aliyah. This study used multiple case study design. Cases studied are the madrasah management models MAN 2 Kudus, MA-NU Banat Kudus and TBSNU Kudus. The research findings indicated that; in the field of planning; Madrasah is able to formulate a collaboration program planning with stakeholders, in a comprehensive manner. In the implementation of the work plan; Principals responsibility is to manage the entire work program, while its implementation is being coordinated by Vice-Principals in accordance with their fields. In the field of monitoring and evaluation; Madrasah always formulates objective, responsible and sustainable monitoring and evaluation plan based on the national standard.